Águila poma: Un paso adelante - CABRERA, SARA NOEMÍ; ZALAZAR, SOFÍA; SCHAAF , ALEJANDRO; GRANDE, JUAN MANUEL (Revista Aves Argentinas, 2026)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).